Canción infantil y las habilidades comunicativas en niños de la institución educativa inicial N°60761 Santa Cecilia, Caballococha 2024 - Leon Farias de Sampayo, Rosalbina (2025)
The objective of this study was to determine the relationship between children's songs and communication skills in the children of the Institución Educativa Inicial N°60761 Santa Cecilia, Caballococha, in the year 2024. It was a quantitative research of a relational nature, with a non-experimental, descriptive and correlational cross-sectional design. The population was made up of 100 children between 3, 4 and 5 years old, belonging to the aforementioned institution. For data collection, the observation technique was used, using an observation guide as an instrument. This instrument was validated by a team of experts with knowledge in the area, guaranteeing that the categories and behaviors observed were relevant and pertinent. The results showed a Spearman correlation coefficient (Rho = 0.745), indicating a high and positive relationship with a statistical significance level of 0.05. In this way, it was concluded that there is a significant positive relationship between the use of children's songs and the communication skills of the children of the Initial Educational Institution N°60761 Santa Cecilia, Caballococha, in 2024.